ANALISIS FUNGSI DAN MAKNA NYANYIAN OKE’ DI MASYARAKAT SEMAU - Yefri Balsomang (Institut Agama Kristen Negeri Kupang, 2022)
The song oke 'is a traditional song from the Semau people, during the ritual of grief, welcoming guests, and praying. In this paper, the writer uses a qualitative approach that is used to generate information from sources. The author uses the semiotic theory to analyze the okay song text ', the weighted scale theory to analyze the melody of okay songs', and the Alan P. Merriam theory to analyze the okay singing function'. This study aims to discuss the function, meaning, and musical form of singing oke '. The function of singing okay 'in the Semau community is in accordance with several functions of music put forward by Alan P. Merriam, namely: (1) entertainment function, (2) communication function, (3) function related to social norms, (4) cultural sustainability function , (4) community integration function, (5) education function. The meaning of okay singing is based on the semiotic theory put forward by Ferdinand De Saussure, namely: (1) as a call of respect, (2) as a sign of request, (3) as a symbol of togetherness, (4) as a figure of speech.